Processing Self-Related Information Under Non-attentional Conditions Revealed by Visual MMN - Cheng, Sizhe; Li, Xinhong; Zhan, Qingchen; Wang, Yapei; Guo, Yaning; Huang, Wei; Cao, Yang; Feng, Tingwei; Wang, Hui; Wu, Shengjun; An, Fei; Wang, Xiuchao; et al. (Frontiers in Human Neuroscience, 2022)
Mismatch negativity (MMN) of event-related potentials (ERPs) is a biomarker reflecting the preattentional change detection under non-attentional conditions. This study was performed to explore whether high self-related information could elicit MMN in the visual channel, indicating the automatic processing of self-related information at the preattentional stage. Thirty-five participants were recruited and asked to list 25 city names including the birthplace. According to the difference of relevance reported from the participants, we divided names of the different cities into high (birthplace as deviants), medium (Xi’an, where participants’ university is located, as deviants), and low (totally unrelated cities as standard stimuli) self-related information. Visual MMN (vMMN) was elicited by high self-related information but not by medium self-related information, with an occipital–temporal scalp distribution, indicating that, under non-attentional condition, high self-related information can be effectively processed automatically in the preattentional stage compared with low self-related information. These data provided new electrophysiological evidence for self-related information processing.